Relationship between Knowledge, Family Support, Frequency of Information, and Attitude Towards Triple Elimination Testing During COVID-19 - Sangguana Marthen Jacobus Koamesah; Idawati Trisno; Su Dji To Rante (Universitas Nusa Cendana, 2021)
East Nusa Tenggara Province is the second-highest province with the percentage of pregnant women having HBsAg reactive (5,26%) and has the lowest screening coverage (4,55%). Increasing the mother’s screening coverage is necessary, followed by increasing access to therapy and early infant detection. A positive attitude should exist to increase the mother’s behavior for assessing triple elimination testing, thus can reduce the transmission risk of Hepatitis B, Syphilis, and HIV-AIDS to the infants. This research analyzed the relationship between knowledge, family support, and information frequency with the mother’s triple elimination testing attitude. This research was an analytical study using the cross-sectional method, conducted at four primary health centres in Kupang city in 2020. The sample selection used a stratified random sampling method, with 110 pregnant women from the four PHC chosen. Data analysis used Chi-square. Results showed only 36,7% of respondents had good triple elimination knowledge, and 33,9% have insufficient knowledge. Most respondents (64%) have a neutral perception, and 27% have a positive perception of family (husband’s) support. 79% of respondents receive scarce information about triple elimination. Respondent’s attitude primarily neutral (61%). However, 23% still have a negative attitude towards triple elimination testing. There is a significant relationship between perception of family support and attitude towards triple elimination testing (p < 0.001). The mother having a positive perception of their husband’s support, also have a positive attitude toward triple elimination testing. Knowledge level and information frequency showed no significant relationship (p = 0.941 and p = 0.093) with mother’s attitude.